ANALYSES OF SOIL WATER CONTENT VARIATIONS AND GPR ATTRIBUTE DISTRIBUTIONS - Schmalz B.; Lennartz B. (My University, 2002)
Water flux was investigated in the frame of the project 'preferential flow paths-3D water and solute dynamic in heterogeneous media'. The objective of the study was the non-destructive three-dimensional monitoring and description of heterogeneous flux fields with hydrological and geophysical methods. A large tank filled with homogeneous sand was set up to realize infiltration experiments. We compared the parameter distribution calculated from measurements of a ground penetrating radar system (GPR) with a simulated water content distribution using a two-dimensional numerical model based on the Van Genuchten-Mualem approach in order to assess the effectiveness of the geophysical measure for the characterization of soil water content variations. A statistical examination of both simulated water contents based on independent measured soil properties and reflection amplitudes from radargrams indicated a better conformity between geophysical data and simulated water contents assuming a heterogeneous hydraulic parameter distribution. The heterogeneous nature of the sand body could be confirmed by dye tracer experiments. The analyzed GPR attribute, the distribution of the maximum reflection amplitudes, may serve in future studies as an indicator for the expected water content heterogeneity in sandy soils.
Keywords: GROUND PENETRATING RADAR; FLUX FIELD; VARIABILITY; SOIL WATER CONTENT